2015
DOI: 10.1016/j.neuroimage.2015.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and thalamic GABA level concentrations play differential roles for the modulation of response selection processes by proprioceptive information

Abstract: The selection of appropriate responses is a complex endeavor requiring the integration of many different sources of information in fronto-striatal-thalamic circuits. An often neglected but relevant piece of information is provided by proprioceptive inputs about the current position of our limbs. This study examines the importance of striatal and thalamic GABA levels in these processes using GABA-edited magnetic resonance spectroscopy (GABAMRS) and a Simon task featuring proprioception-induced interference in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 52 publications
(80 reference statements)
1
40
0
Order By: Relevance
“…Similar to what we observed here between GABA and CS excitability, these other processes may also be sensitive to GABA availability. Interestingly, our findings were regionally specific to M1, similar to other reports relating GABA concentrations to physiological or behavioral measures (Grachev and Apkarian, 2000;Grachev et al, 2001;Boy et al, 2011;Dharmadhikari et al, 2015;Durst et al, 2015;Heba et al, 2016;Mikkelsen et al, 2016). GABA concentration in the three other cortical regions measured showed no relationship with CS excitability.…”
Section: Intrinsic Corticospinal Excitability and Reaction Timesupporting
confidence: 90%
“…Similar to what we observed here between GABA and CS excitability, these other processes may also be sensitive to GABA availability. Interestingly, our findings were regionally specific to M1, similar to other reports relating GABA concentrations to physiological or behavioral measures (Grachev and Apkarian, 2000;Grachev et al, 2001;Boy et al, 2011;Dharmadhikari et al, 2015;Durst et al, 2015;Heba et al, 2016;Mikkelsen et al, 2016). GABA concentration in the three other cortical regions measured showed no relationship with CS excitability.…”
Section: Intrinsic Corticospinal Excitability and Reaction Timesupporting
confidence: 90%
“…Abnormalities in GABA concentrations have been associated with neurological diseases and trauma (Blicher et al, 2015; Dharmadhikari et al, 2015; Draper et al, 2014; Hattingen et al, 2014; van der Hel et al, 2013). Given the reliability observed here in healthy individuals, it may be possible to relate local changes in GABA to patterns of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…In previous human studies, GABA levels in the striatum or putamen have been reported to be either reduced (22), unaltered (14) or elevated (13,23) in PD compared with healthy controls. Similarly, either elevated BG GABA levels (24,25) or reduced left striatum GABA levels (26) have been reported in animal studies.…”
Section: Discussionmentioning
confidence: 94%
“…Firstly, a larger VOI (included striatum, globus pallidus, part of thalamus, and other gray- and white-matter structures) was chosen for our study (3 × 3 × 2 cm 3 ) because of the different data acquisition strategy. Indeed, thalamic GABA levels in references (22) and (14) are significantly reduced. Secondly, there are differences between methodologies – our study is closest in methodology to (14).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation